A new method for studying sub‐pulse dynamics at synchrotron sources. (7th August 2015) - Wingert, James; Singer, Andrej; Shpyrko, Oleg G.
<x xml:space="preserve">Abstract</x> The possibility of studying dynamics at time scales on the order of the pulse duration at synchrotron X‐ray sources with present avalanche photodiode point detection technology is investigated, without adopting pump–probe techniques. It is found that sample dynamics can be characterized by counting single and double photon events and an analytical approach is developed to estimate the time required for a statistically significant measurement to be made. The amount of scattering required to make such a measurement possible presently within a few days is indicated and it is shown that at next‐generation synchrotron sources this time will be reduced dramatically, i.e. by more than three orders of magnitude. The analytical results are confirmed with simulations in the frame of Gaussian statistics. In the future, this approach could be extended to even shorter time scales with the implementation of ultrafast streak cameras.